2022
DOI: 10.1039/d2qi01165d
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating BiVO4/FeOOH/ZnFe-LDH hierarchical core–shell nanorod arrays for visible-light-driven photoelectrochemical water oxidation

Abstract: In this paper, porous BiVO4 nanorod arrays were encapsulated with FeOOH and ZnFe layered double hydroxide (ZnFe LDH) for the construction of hierarchical structure to achieve excellent transfer and separation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition, the charge transfer efficiency of the synthesized samples was further evaluated by electrochemical impedance testing. As shown in Figure b, the arc radius of CPB/IO-2 is significantly smaller than that of pure In 2 O 3 and CsPbBr 3 QDs, indicating that the CPB/IO-2 could decrease the charge transfer resistance and suppress the photoinduced charge recombination. …”
Section: Resultsmentioning
confidence: 96%
“…In addition, the charge transfer efficiency of the synthesized samples was further evaluated by electrochemical impedance testing. As shown in Figure b, the arc radius of CPB/IO-2 is significantly smaller than that of pure In 2 O 3 and CsPbBr 3 QDs, indicating that the CPB/IO-2 could decrease the charge transfer resistance and suppress the photoinduced charge recombination. …”
Section: Resultsmentioning
confidence: 96%
“…The photocurrent of TCP, Cd 0.6 Zn 0.4 S, and TCP@CZS-3 with five light on–off cycles is displayed in Figure a. The photocurrent density of TCP@CZS-3 is much higher than that of pristine Cd 0.6 Zn 0.4 S and TCP, strongly illustrating that incorporation of TCP into Cd 0.6 Zn 0.4 S can efficiently promote the generation and migration of the photoexcited charge. Furthermore, the EIS Nyquist diagrams of TCP, Cd 0.6 Zn 0.4 S, and TCP@CZS-3 are in accord with the results of the photocurrent response (Figure b). TCP@CZS-3 exhibits the smallest semicircle compared with bare TCP and Cd 0.6 Zn 0.4 S, revealing that this catalyst can reduce the interfacial charge-transfer resistance .…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure a, the transient photocurrent responses of Ni–Al LDHs, ZnIn 2 S 4 , ZNA, and CDsZNA were measured under intermittent visible-light irradiation cycles. The pure Ni–Al LDHs and ZnIn 2 S 4 exhibit lower current intensity caused by the high recombination rate of charge carriers . The ZNA catalyst exhibits the enhancement of photocurrent intensity, in comparison with Ni–Al LDHs and ZnIn 2 S 4 , indicating that the construction of ZNA heterojunction can boost charge transfer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…After the incorporation of CDs in ZNA, the PL intensity of 3-CDsZNA is significantly quenched, and 3-CDsZNA presents the lowest PL intensity, consistent with the results of H 2 performance. It is concluded that the loaded CDs and Ni− Al LDHs have a positive effect on the inhibition of fast charge 57 The ZNA catalyst exhibits the enhancement of photocurrent intensity, in comparison with Ni−Al LDHs and ZnIn 2 S 4 , indicating that the construction of ZNA heterojunction can boost charge transfer. Importantly, after the incorporation of CDs into ZNA, CDsZNA presents further improved photocurrent density, implying that CDs with electron migration and storage properties promote visiblelight absorption and enhance charge generation.…”
Section: Photocatalytic Mechanismmentioning
confidence: 92%